Araucaria araucana tree-ring chronologies in Argentina: spatial growth variations and climate influences - Mundo, Ignacio Alberto (2011)
Seventeen tree-ring chronologies from the conifer Araucaria araucana (Molina) K. Koch have been analyzed across its range of distribution in Argentina. We studied the growth patterns and determined the main climatic factors influencing A. araucana radial growth. All the chronologies show a strong common signal observed by the high amount of variance explained by the first principal component (PC1) and the high mean correlation (r = 0.597) between the chronologies over the 1676–1974 interval. On this basis, we developed a regional chronology that is 866 years long (A.D. 1140–2006) and includes 621 tree-ring series. Based on the PC2 scores, chronologies were clearly separated by elevation in high- and low-elevation records. Regional tree growth is strongly negatively related to temperatures during summer and fall in the previous-growing season and spring in the current-growing season, respectively. A positive association of tree growth with precipitation is recorded during spring in the current growing season. These results suggest a close relationship between A. araucana tree growth and water availability on a regional scale. This observation is also consistent with a positive and significant correlation between our A. araucana regional record and a reconstruction of November–December rainfall for northern Patagonia inferred from the xeric Austrocedrus chilensis during the past 400 years. Negative correlations between A. araucana regional growth and the sea surface temperature in the Nino 3.4 region reflect the occurrence of above-mean summer temperatures in the region during positive tropical Pacific SST anomalies. The negative relationship with the Antarctic Oscillation (AAO) results from reduced precipitation in our study region during the positive phase of the AAO. The effect of elevation on water availability is consistent with significant correlations between ring-width variations at lower elevations and the Palmer Drought Severity Index during spring and summer in the current growing season. Our study emphasizes the high dendroclimatological potential of A. araucana chronologies for reconstructing past climate variations in northern Patagonia during the past millennium.